Blood Transfusion Errors Within a Health System: A Review of Root Cause Analyses. - Lancaster, Elizabeth A.; Rhodus, Elizabeth K.; Duke, Mary B.; Harris, Andrew M. (Patient Safety (2689-0143), 2021)
Introduction Blood transfusions are lifesaving treatments which require critical attention to processes and details. If processes are not followed, grievous errors can lead to sentinel events. A review of investigations completed due to reported events will show the error trends associated with systems used throughout the blood transfusion process. Methods This study employed root cause analyses (RCAs) within the Veterans Health Administration (VHA) to review the events leading to blood transfusion errors. Data was pulled from the RCA databases within the VA National Center for Patient Safety. The time frame was October 2014 to August 2019. A total of 53 RCAs and aggregated reviews were included in the study. These were reviewed for common themes and gaps present within processes. Results The most common events fell within the categories of incorrect or delayed blood orders, incorrect or lack of patient identification, and wrong blood given. The RCA for each event was reviewed and studied. The RCAs had a crossover of multiple causes; lack of a formal process, communication barriers, and technology barriers were the most frequent. Conclusion These RCAs express great variation between VHA facilities, such as process created, number of staff reports, and number of RCAs completed. Lack of standard practices nationwide, training barriers, and technology barriers may explain the variation of transfusion errors throughout the VHA. This study brings to light questions about standardization of transfusion protocols. Future study regarding such standardization is necessary to determine its plausibility.